Student response to digital books In class x swimming subject - Whilis Pitaloka; Hadi Suhendro (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The Physical Education, Sports and Health learning guide is only a textbook containing material and movement pictures. Meanwhile, in this day and age, the average student already has a gadget that they always carry everywhere, students need media as a guide that can be carried and easy for students to access and they can observe the complete series of movements. The purpose of this research is to determine students' responses to digital books. The method used in this research is quantitative descriptive. The research results showed a positive response after learning with digital books with a percentage reaching 93.98% from 33 students.